Antiphospholipid syndrome in lupus retinopathy - Hong-Kee N (Dove Medical Press, 2014)
Ng Hong-Kee,1,2 Chong Mei-Fong,2 Yaakub Azhany,1 Embong Zunaina1 1Department of Ophthalmology, School of Medical Sciences, Universiti Sains Malaysia, Kubang Kerian, Kelantan, Malaysia; 2Department of Ophthalmology, Hospital Raja Permaisuri Bainun, Ipoh, Perak, Malaysia Abstract: Systemic lupus erythematosus (SLE) is a chronic, multisystem, autoimmune disease that can affect any part of the human body including the eyes. Common blinding ocular manifestations include central retinal artery occlusion (CRAO), central retinal vein occlusion (CRVO), severe vaso-occlusive retinopathy, and optic nerve involvement. Antiphospholipid syndrome (APS) in lupus is usually associated with large vessel occlusions and needs prompt treatment with anticoagulant. We are reporting two cases of APS in SLE patients that presented with CRVO (case 1) and vaso-occlusive lupus retinopathy (case 2). Both cases were positive for antiphospholipid antibody (APA) and were treated with immunosuppression, anticoagulant, and laser treatment. Thus, screening for APA is vital in SLE patients with lupus retinopathy, as prompt treatment with anticoagulants is important to prevent further vascular thrombosis, which worsens the visual prognosis. Keywords: systemic lupus erythematosus, antiphospholipid antibody, central retinal vein occlusion, vaso-occlusive retinopathy